Earthquake Processes: Physical Modelling, Numerical Simulation and Data Analysis Part II 2002
DOI: 10.1007/978-3-0348-8197-5_15
|View full text |Cite
|
Sign up to set email alerts
|

Long-range Automaton Models of Earthquakes: Power-law Accelerations, Correlation Evolution, and Mode-switching

Abstract: -We introduce a conceptual model for the in-plane physics of an earthquake fault. The model employs cellular automaton techniques to simulate tectonic loading, earthquake rupture, and strain redistribution. The impact of a hypothetical crustal elastodynamic Green's function is approximated by a long-range strain redistribution law with a r Àp dependance. We investigate the influence of the effective elastodynamic interaction range upon the dynamical behaviour of the model by conducting experiments with differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Recent observations of growing correlation lengths in seismicity data prior to large earthquakes provide additional support for the critical point hypothesis for earthquakes (ZOELLER et al, 2001). Studies of different classes of CA models indicate that the stress field may evolve like that of critical point system or selforganized critical systems, depending on the rules used in the CA model to approximate the rupture and stress redistribution processes (SAMMIS and SMITH, 1999;WEATHERLEY et al, 2000WEATHERLEY et al, , 2002. Here we study the evolution in the stress correlation function in a physically based numerical model which accurately simulates the elasto-dynamics of a stress transfer and rupture in simplified 2-D systems (MORA and PLACE, 1994;PLACE and MORA, 1999).…”
Section: Introductionmentioning
confidence: 94%
“…Recent observations of growing correlation lengths in seismicity data prior to large earthquakes provide additional support for the critical point hypothesis for earthquakes (ZOELLER et al, 2001). Studies of different classes of CA models indicate that the stress field may evolve like that of critical point system or selforganized critical systems, depending on the rules used in the CA model to approximate the rupture and stress redistribution processes (SAMMIS and SMITH, 1999;WEATHERLEY et al, 2000WEATHERLEY et al, , 2002. Here we study the evolution in the stress correlation function in a physically based numerical model which accurately simulates the elasto-dynamics of a stress transfer and rupture in simplified 2-D systems (MORA and PLACE, 1994;PLACE and MORA, 1999).…”
Section: Introductionmentioning
confidence: 94%
“…It is also necessary to clearly understand the mechanical interactions within a given fault network, in order to possibly achieve earthquake prediction or forecasting with a reasonable accuracy, both in the space and time dimensions. On more fundamental grounds, understanding the relationships between faults (or more generally earthquake generating cluster centers) at different scales can help to develop a metatheory based on the renormalization group approach [ Wilson , 1975; Allégre et al , 1982] to advance on the understanding and modeling of seismicity and rupture processes as a critical phenomenon [ Sornette , 2006; Bowman et al , 1998; Weatherley et al , 2002], as the size of an upcoming event may be correlated with the range of scales over which earthquake clustering properties change collectively (thus yielding a measure of the correlation length).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, using a cellular automaton model, Weatherly et al (2002) showed that the overall behaviour of seismicity depends strongly on the exponent of the elastic Green's function (that we took equal to 3, that is, corresponding to a rather short interaction range). In particular, they showed that for this value of 3 for the exponent they did not observe any critical behaviour before a large event.…”
Section: Interpretation and Discussionmentioning
confidence: 99%